Efecto de extractos vegetales en el control de trips (Frankliniella occidentalis), en condiciones de laboratorio, Cantón Latacunga, Provincia de Cotopaxi, 2022. - Chuya Tonato, Kleber Mauricio (2022)
The purpose of this research was to evaluate the effect of plant extracts on the control of thrips (Frankliniella occidentalis), under laboratory conditions, where it was determined which of the extracts and concentrations in the study presented better control, to be considered as an alternative for the management of the pest, and also the one that is more friendly to the environment at the moment of application, for which a completely randomized experimental design with six treatments and six repetitions was used. First, the elaboration of the vegetal extracts was carried out, and then the thrips count was carried out too in order to introduce 15 individuals in each experimental unit, which was applied at two concentrations (Conium maculatun) Hemlock at 25% and 50%, and (Nicotiana glauca) False tobacco at 25% and 50%, the witness was given the same conditions as the experimental units to be evaluated. After this, we proceed with the application of the extract with an atomizer to each experimental unit. Finally, after the application of the plant extracts, data collection was carried out after having applied the plant extract 3 times, for which a time of 10 minutes was taken to perform the count, after the first three hours of having performed the count was carried out every 3 hours for 18 hours, keeping its record in a field book. Then we proceeded to evaluate and tabulate the registered data of the investigation in the statistical program Infostat in order to determine which extract and what concentration has better control in thrips, where the following results were obtained: the average with the highest percentage of control during the first 3 hours was for (Conium maculatun) Hemlock at 50% with an average of 4.67 dead individuals, which represents a percentage of 38.9%, followed by the extract (Nicotiana glauca) False tobacco at 50% with an average of 3, 72 dead individuals, which represents a percentage of 24.8%. Therefore, it is recommended to use the hemlock extract with a concentration of 50%, with which better results were obtained.